2016
DOI: 10.1021/acs.organomet.6b00085
|View full text |Cite
|
Sign up to set email alerts
|

Acceptorless Dehydrogenation of Alcohols on a Diruthenium(II,II) Platform

Abstract: The diruthenium(II,II) complex [Ru 2 (L 1 )(OAc) 3 ]Cl (1), spanned by a naphthyridine-diimine ligand and bridged by three acetates, has been synthesized. The catalytic efficacy of complex 1 has been evaluated for the acceptorless dehydrogenation (AD) of alcohols and for the dehydrogenative coupling reactions of alcohols with Wittig reagents. The diruthenium(II,II) complex is an excellent catalyst for AD of a diverse range of alcohols, and it is shown to be particularly effective for the conversion of primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 121 publications
2
68
1
Order By: Relevance
“…The rigid naphthyridine core promotes a close interaction between two transition metals, and additional donor groups may be incorporated to enforce open binding sites for exploration of metal‐metal cooperativity in reaction chemistry . Moreover, naphthyridine‐based bimetallic complexes have been shown to catalyze a range of reactions . However, these mostly symmetrical systems have so far been used to study homobimetallic complexes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rigid naphthyridine core promotes a close interaction between two transition metals, and additional donor groups may be incorporated to enforce open binding sites for exploration of metal‐metal cooperativity in reaction chemistry . Moreover, naphthyridine‐based bimetallic complexes have been shown to catalyze a range of reactions . However, these mostly symmetrical systems have so far been used to study homobimetallic complexes.…”
Section: Methodsmentioning
confidence: 99%
“…[21] Rigid, naphthyridine-based ligands are suitable candidates for addressing these issues. [26][27][28][29][30][31] However, these mostly symmetrical systems have so far been used to study homobimetallic complexes. [23][24][25] Moreover,n aphthyridine-based bimetallicc omplexes have been shown to catalyzearange of reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such reactions have potential applications in hydrogen energy storage, and readily available alcohols can serve as important sources for liquid organic hydrogen carriers which can be easily implemented in liquid fuel infrastructure , . In recent years, AAD reaction has made significant progresses, using not only noble metals (Ru, Ir, Rh, and Re) but also earth‐abundant base metals (Fe, Co, Cu, Ni, and Mn).…”
Section: Introductionmentioning
confidence: 99%
“…13 Recently, expensive metal catalyst gold/palladium bimetallic nanoparticles were utilized to catalyze the tandem process of aerobic oxidation and Horner-Wadsworth-Emmons olefination, 14 where 1.5 equivalents of triethyl phosphonoacetate and 3 equivalents of base were added to promote the reaction smoothly. Bera and co-workers reported that a diruthenium complex catalyzed the dehydrogenative coupling reactions of alcohols with Wittig reagents, 15 where the starting material for making the catalyst was commercially unavailable, and its preparation procedure was not easy. Therefore, developing a facile, efficient, and environmentally friendly synthesis of the C=C bond using the method of oxidation-Wittig tandem reaction is still highly desired.…”
mentioning
confidence: 99%